Experimental observation of open structures in elemental magnesium at terapascal pressures - Gorman, MG; Elatresh, S; Lazicki, A; Cormier, MME; Bonev, SA; McGonegle, D; Briggs, R; Coleman, AL; Rothman, SD; Peacock, L; Bernier, JV; Coppari, F; et al. (Springer Nature, 2022)
Investigating how solid matter behaves at enormous pressures, such as those found in the deep interiors of giant planets, is a great experimental challenge. Over the past decade, computational predictions have revealed that compression to terapascal pressures may bring about counter-intuitive changes in the structure and bonding of solids as quantum mechanical forces grow in influence1,2,3,4,5,6. Although this behaviour has been observed at modest pressures in the highly compressible light alkali metals7,8, it has not been established whether it is commonplace among high-pressure solids more broadly. We used shaped laser pulses at the National Ignition Facility to compress elemental Mg up to 1.3 TPa, which is approximately four times the pressure at the Earth’s core. By directly probing the crystal structure using nanosecond-duration X-ray diffraction, we found that Mg changes its crystal structure several times with non-close-packed phases emerging at the highest pressures. Our results demonstrate that phase transformations of extremely condensed matter, previously only accessible through theoretical calculations, can now be experimentally explored.